Anxiety and defense mechanisms of Hyojang characters in movie 사도 (Sado) - Azizah Intan Kartini (Universitas Pendidikan Indonesia (UPI), 2023)
In 1757, Crown Prince Hyojang, son of King Yeongjo, suffered from a severe anxiety disorder. This illness can be seen in the movie Sado by Lee Jeon-ik released in 2015. The main character of the movie Sado is a representative of Prince Hyojang, who is described as experiencing anxiety which puts pressure on his father. Therefore, this study explores why they implement defense mechanisms against anxiety experienced by individuals. Driven by these problems, this research through literature focuses on two problems; how anxiety is shown by Hyojang's character in the movie Sado and how the defense mechanism is shown by Hyojang's character in the movie Sado. This research is qualitative research using descriptive methods with a literature psychology approach and psychoanalytic theory developed by Freud. The results of this research are as follows; First, the main character Hyojang in the movie Sado experiences three forms of anxiety which are realistic anxiety, neurotic anxiety, and moral anxiety; Second, Hyojang’s subconsciousness is described as carrying out three forms of defense mechanisms that are displacement, reaction formation, and repression.